How Students Define Success Differently for Classes They Like or Dislike - Tim Urdan; Daniel Teramoto (MDPI AG, 2023)
Most of the research examining student motivation, particularly achievement goals, has relied on experimental or survey methods that narrow the number and type of goals students can report. A few researchers have asked students open-ended questions, either using surveys or interviews, about what they want to accomplish and their reasons for studying or trying to achieve. These studies have generally found a larger number of goals across a broader set of categories (e.g., social-comparison, internal standard, social, work-avoidance, utilitarian) than is typically examined in research on achievement goals. In this study, we asked a sample of 152 undergraduate students at one university in California (USA) to describe how they defined success in two different classes: One they liked and one they disliked. Our objectives were to examine how students described their definitions for success, whether those definitions differed for liked and disliked classes, and to learn about students' perceptions regarding the sources of their definitions of success. The results indicated that students' definitions of success were more varied in classes they liked than in those they disliked. In addition, their definitions focused more on developing competence and positive relationships with the teacher in classes they liked, but they focused on getting a good grade, completing the class, and avoiding work in classes they disliked. The results also indicated that students perceived different sources of the same definitions of success for liked and disliked classes, with a greater emphasis on bad teaching and difficult course material in the disliked class. The implications for conceptualizing the methodology for studying achievement goals are discussed.